Evaluation of mechanical properties and anisotropy of ultra-fine grained 1050 aluminum sheets produced by incremental ECAP. (15th September 2017) - Ciemiorek, M.; Chrominski, W.; Olejnik, L.; Lewandowska, M.
Abstract: Rectangular plates of technically pure 1050 aluminum processed by Incremental Equal Channel Angular Pressing were evaluated in terms of anisotropy and formability. After 8 passes, the plates exhibit in planar and through thickness isotropy which manifest by the independence of YS, UTS and rα -values on the testing direction and fairly uniform distribution of microhardness across thickness. Such properties were attributed to randomized texture developed during processing and uniform microstructure with ultrafine equiaxed grains in all three plate's planes. The values of the parameters describing ability for deep drawing are very promising as r values only slightly decrease with I-ECAP passes while they became independent on testing direction. This indicates that although the processed plates are slightly prone to wall thinning (typical for aluminum alloys), they are resistant to earing formation, which is one of the main technological problem in deep drawing. The combination of isotropic parameters, enhanced mechanical strength and suitable ability to deep drawing may yield attractive products with a considerable potential for further forming. Graphical abstract: Highlights: Incremental Equal Channel Angular Pressing of 1050 aluminum sheet lead to in-planar and through thickness isotropy. YS, UTS and Lankford parameter are independent on the testing direction due to equiaxed grains and randomized texture. The values of the Lankford parameter are similar to coarse-grained aluminum alloys and indicate that earing tendency is reduced.